#### Answer

$x^{2}-1$

#### Work Step by Step

We are given that $f(x)=x^{2}+4$, $g(x)=2x+3$, and $h(x)=x-5$.
We are asked to find $(h∘f)(x)$. We know that $(h∘f)(x)=h(f(x))$.
Therefore, $(h∘f)(x)=h(x^{2}+4)=(x^{2}+4)-5=x^{2}+4-5=x^{2}-1$.

Published by
Pearson

ISBN 10:
0321969359

ISBN 13:
978-0-32196-935-4

$x^{2}-1$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.